2008
DOI: 10.1080/01443610802463710
|View full text |Cite
|
Sign up to set email alerts
|

Fetal congenital anomalies diagnosed by ultrasound in Asian and non-Asian women

Abstract: The incidence of congenital heart defects in Asian children is significantly higher than in non-Asian, however little data are available for other anomalies. The Fetal Management Unit at St Mary's Hospital is a tertiary referral centre for prenatal diagnosis in the north-west region. Using data collected after routine prenatal ultrasonography between 1996-2001, we show that in a defined population there was a significant reduction in the incidence of central nervous system (CNS) anomalies over this period but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In most of the studies, central nervous system anomalies appear to be the most common systemic congenital anomalies. 18 The incidence of central nervous system anomaly observed in this study (49.13/10000 women) was almost similar to the study reported by Atkinson et al 19 (44/10000 women). A study from Nepal also found central nervous system anomalies as the most common with higher frequencies of anencephaly followed by hydrocephalus and meningomyelocele and other major defects were related to gastrointestinal, musculoskeletal and genitourinary system.…”
Section: Discussionsupporting
confidence: 90%
“…In most of the studies, central nervous system anomalies appear to be the most common systemic congenital anomalies. 18 The incidence of central nervous system anomaly observed in this study (49.13/10000 women) was almost similar to the study reported by Atkinson et al 19 (44/10000 women). A study from Nepal also found central nervous system anomalies as the most common with higher frequencies of anencephaly followed by hydrocephalus and meningomyelocele and other major defects were related to gastrointestinal, musculoskeletal and genitourinary system.…”
Section: Discussionsupporting
confidence: 90%
“…An estimated 6% children worldwide are born with congenital anomalies 11 . Frequency and pattern of congenital anomalies depends on many factors like cultural, environmental and socio economic [12][13][14] . Chromosomal problems and exposure to medicines, chemicals and other toxic substances also play role in congenital birth defects [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%